Plan de marketing para la empresa Infocentro de Ventanas, provincia de Los Ríos - Pérez Arroba, Rocio Irlanda (2013)
The research started because of the problem that appeared inside the company INFOCENTRO in the city of Ventanas. The problem was based in the fact that there are not any marketing strategies that allow the company improving its market share. As a first step it was formulated the investigation problem: How does the lack of a marketing plan affect the sales of the INFOCENTRO in Ventanas? Once the problem was formulated, the objectives were determined. The main objective of the investigation was: To elaborate the marketing plan for INFOCENTRO in Ventanas, Los Ríos. The sources of investigation that were used to get the needed data were primary and secondary sources. The first one was accomplished by a group of question designed to be applied in a survey for the clients of the company and also in an interview with the manager. The secondary sources allowed the researcher get into the existing documentation about subjects as: marketing plan, after sales service, human resources training, market analyze, execution and control of the consumers, market research, positioning strategies, and others. All the information got, thanks to the surveys, interviews and documental research, allowed the researcher to suggest a potential solution to the problem. The solution is focused on the design of a marketing plan that allows organizing the strategies that are going to be applied and the company image in Ventanas.